2013
DOI: 10.1007/s10549-013-2600-4
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory breast cancer (IBC): clues for targeted therapies

Abstract: Inflammatory breast cancer (IBC) is the most aggressive type of advanced breast cancer characterized by rapid proliferation, early metastatic development and poor prognosis. Since there are few preclinical models of IBC, there is a general lack of understanding of the complexity of the disease. Recently, we have developed a new model of IBC derived from the pleural effusion of a woman with metastatic secondary IBC. FC-IBC02 cells are triple negative and form clusters (mammospheres) in suspension that are stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
81
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 35 publications
1
81
0
1
Order By: Relevance
“…Furthermore, other studies have unequivocally demonstrated the presence of E-cadherin in a percentage of both primary breast tumors and distant metastases (48) and a correlation between cellular aggregation and successful metastasis was first published over 50 years ago (49,50). More recent studies examining circulating tumor cells (CTCs) have provided evidence that these cells often exist in the bloodstream as multicellular aggregates (29,51,52). Our data may help explain the significance of these findings in that aggregation may occur in CTCs and may facilitate metastasis through the inhibition of anoikis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other studies have unequivocally demonstrated the presence of E-cadherin in a percentage of both primary breast tumors and distant metastases (48) and a correlation between cellular aggregation and successful metastasis was first published over 50 years ago (49,50). More recent studies examining circulating tumor cells (CTCs) have provided evidence that these cells often exist in the bloodstream as multicellular aggregates (29,51,52). Our data may help explain the significance of these findings in that aggregation may occur in CTCs and may facilitate metastasis through the inhibition of anoikis.…”
Section: Discussionmentioning
confidence: 99%
“…The biology of breast cancer is complex, involving oncogenesis, evasion of host immune defense mechanisms, angiogenesis, invasion and metastasis . Recently, the contribution of interleukins, pleiotropic cytokines, to cancer progression has been demonstrated (Fernandez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, the pathological and molecular underpinnings of the disease contribute to the poor prognosis of IBC patients relative to other, more common subtypes of human breast cancer (8). Therefore IBC is unequivocally considered a formidable clinical challenge in contemporary cancer medicine (2)(3)(4)(5)(6)(7)(8). Within this clinical context, the emerging field of "theranostic" (a combination of the terms "therapeutic" and "diagnostic") approaches offers an attractive avenue for the concurrent detection and treatment of cancer.…”
mentioning
confidence: 99%